Penerapan model kolaboratif dalam kebijakan data tunggal industri emas bagi penerimaan negara dengan pendekatan multi helix - Fahmi, Helmi Satria; Adriyanto, Arzhat Rizal; Asropi (Directorate General of Taxes, 2024)
Indonesia is one of the largest gold producing countries in the world. Based on mineral commodity data, Indonesia’s gold reserves reached 2,600 tons. In addition, the mining production reached 66 metric tons in 2021 and 70 metric tons in 2022. However, there are various problems and challenges related to efforts to utilize gold minerals, one of which is the limited availability and validity data. Therefore, this research aims to analyze how a collaboration model related to the gold industry’s single data policy for tax purposes can be implemented using a Multi Helix approach. In the Multi Helix concept, the role of each actor has very close participation to create success in creating quality data in the gold industry sector and sustainable development. Furthermore, it is expected to contribute significantly to tax revenues. Aside from that, the existence of the SDI policy is intended to provide benefits for sustainable economic development by maintaining a good quality of environmental ecosystems. Additionally, SDI data is expected to have a hand in state revenues both in the form of taxes and royalties to the state optimally, thereby creating competitive and growing businesses.